2020
DOI: 10.1177/1756286419895155
|View full text |Cite
|
Sign up to set email alerts
|

PPMS onset upon adalimumab treatment extends the spectrum of anti-TNF-α therapy-associated demyelinating disorders

Abstract: Since their introduction in 1999, anti-tumour necrosis factor-α (anti-TNF-α) therapies have been suspected repeatedly to be associated with the occurrence of central nervous system (CNS) demyelinating disorders, including multiple sclerosis (MS). However, recent publications were restricted to descriptions of monophasic demyelinating events or cases of relapsing–remitting MS (RRMS). We here provide the first case report of primary progressive MS (PPMS) onset upon anti-TNF-α therapy as well as a literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Based on current knowledge of TNF biology, a possible explanation for these results, which at that time were quite unexpected, could be linked to the pleiotropic actions of TNF, including both pro- and anti-inflammatory functions as well as the almost ubiquitous expression and action of such cytokine. Moreover, the relationship between nonselective TNF inhibitors and MS is further supported by several cases of MS onset observed in patients with other diseases [ 192 , 193 ]. Patients with rheumatoid arthritis treated with either etanercept or infliximab showed new-onset neurologic signs and symptoms, associated with demyelinating lesions of the CNS [ 194 ] or symptoms fulfilling the criteria for clinically definite RRMS [ 195 ].…”
Section: Targeting Tnf Signaling As a Therapy For Msmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on current knowledge of TNF biology, a possible explanation for these results, which at that time were quite unexpected, could be linked to the pleiotropic actions of TNF, including both pro- and anti-inflammatory functions as well as the almost ubiquitous expression and action of such cytokine. Moreover, the relationship between nonselective TNF inhibitors and MS is further supported by several cases of MS onset observed in patients with other diseases [ 192 , 193 ]. Patients with rheumatoid arthritis treated with either etanercept or infliximab showed new-onset neurologic signs and symptoms, associated with demyelinating lesions of the CNS [ 194 ] or symptoms fulfilling the criteria for clinically definite RRMS [ 195 ].…”
Section: Targeting Tnf Signaling As a Therapy For Msmentioning
confidence: 97%
“…Patients with rheumatoid arthritis treated with either etanercept or infliximab showed new-onset neurologic signs and symptoms, associated with demyelinating lesions of the CNS [ 194 ] or symptoms fulfilling the criteria for clinically definite RRMS [ 195 ]. More recently, a case report showed a 51-year old male patient treated for a psoriasis arthritis with an anti-TNF agent, adalimumab, developed slowly progressing neurological deficits about 18 months after treatment initiation [ 192 ]. Overall these studies suggested that nonselective inhibition of TNF is harmful both in MS and in other inflammatory disease, but at the same time highlight the relevance of TNF in the pathophysiology of MS. Current guidelines suggest to avoid the use of anti-TNF drugs in individuals with a history of MS or demyelinating disease and patients with inflammatory disease should be carefully monitored with frequent MRI regardless of their clinical status in order to prevent the occurrence of MS.…”
Section: Targeting Tnf Signaling As a Therapy For Msmentioning
confidence: 99%
“…For one, anti-TNF therapy has been associated with a 250% increase in the occurrence of tuberculosis (46). Furthermore, these therapies have been reported to trigger multiple sclerosis (MS) and other demyelinating conditions (47)(48)(49)(50). This is in line with the reported disease worsening in patients with pre-existing MS in clinical trials for Lenercept and cA2, two types of anti-TNF therapy (51,52).…”
Section: Segrms: the Unmet Medical Needmentioning
confidence: 78%
“…4 Until now, about 20 MS case reports have been related to anti-TNFa treatment and Engel et al described the first case of PPMS under adalimumab treatment. 10 Actually, several hypotheses have been proposed to explain a potential biological relationship between TNFα blockers and demyelinating disease. TNFα blockers can exacerbate CNS demyelination by decreasing TNFR2 receptors, which are necessary for the proliferation of immature oligodendrocytes and myelin repair.…”
Section: Discussionmentioning
confidence: 99%
“… 15 On the other hand, growing clinical reported evidence, and recently, a link between the development of MS and the presence of the single nucleotide polymorphism (SNP), suggest an etiological role of anti-TNF drugs in. 10 …”
Section: Discussionmentioning
confidence: 99%